Understanding psychology - Morris, Charles G. (Prentice Hall, 1999)
Understanding Psychology presents introductory psychology as a science, providing engaging coverage of all traditional topics and giving readers a firm grasp of the scope, vocabulary, and concepts of the discipline. It treats psychology as a diverse discipline - the way psychologists perceive it - combining a concern for research, theory, gender, and cross-cultural issues with examples that are both familiar and applicable to users, inspiring critical thought and analysis of ideas presented.